Simplification of Marketing Scheme for Business Start-Ups - Soviar, Jakub (Communications - Scientific letters of the University of Zilina, 2011)
This paper deals with the topic of marketing planning simplification in order to use it for start-ups in the field of small & medium enterprises. There are 11 main question areas which can be used for logical and empiric marketing approaches. These questions are elaborated on the basis of standard marketing planning methods and approaches from the literature given in references.